1997
DOI: 10.1007/bf02505688
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of [3H]-cycloalkanoprogesterones (pregna-d'-pentaranes) and study of their interaction with a progesterone receptor

Abstract: tn order to search target organs and to study the mechanism of the action of steroids with separated biological functions, tritium-labeled pregna-D'-pentaranes were synthesized by an original procedure, and their interaction with a progesterone receptor was investigated. The uterine progesterone receptor was shown to be the only specific binding protein for these compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…More detailed study of PR binding using tritium-labeled pentaranes 1 and 2 showed that this contradiction appears to arise from overestimation of the active concentration of the hydrophobic pentaranes due to high adsorption on tube walls (4). To obtain reliable data on binding of pentaranes to PR and account for their adsorption on tube walls it was necessary to use tritiated pentaranes with a relatively high specific radioactivity (5).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More detailed study of PR binding using tritium-labeled pentaranes 1 and 2 showed that this contradiction appears to arise from overestimation of the active concentration of the hydrophobic pentaranes due to high adsorption on tube walls (4). To obtain reliable data on binding of pentaranes to PR and account for their adsorption on tube walls it was necessary to use tritiated pentaranes with a relatively high specific radioactivity (5).…”
Section: Methodsmentioning
confidence: 99%
“…Lindlar catalyst and tris-triphenylphosphine (I) rhodium chloride were purchased from Fluka. Standard steroids were synthesized as described earlier (5). Analysis and purification of preparations was performed by HPLC and TLC (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…133 The preparation of various 16a,17a-isooxazoline derivatives of prednisolone such as 65 has been reported 134,135 in the course of work on novel antiinflammatory steroids whilst work on the synthesis of 16a,17acyclohexanopregnanes such as 66 and their interaction with the progesterone receptor, has continued. 136,137 The introduction of functionality at C-21 is important in the context of a number of steroidal biological activities. The effect of C-16 substituents on the formation of C-20 silyl 20(21)-enol ethers has been examined.…”
Section: Pregnanesmentioning
confidence: 99%